Hotel Rwanda [videorecording (DVD)] - Guerra, Andrea, 1961-; Gregson-Williams, Rupert (MGM DVD., 2005)
Based on the true story of Paul Rusesabagina, a five-star-hotel manager who uses his wits and persuasion in striving to save more than 1,200 Tutsis and Hutus from being massacred by the Interahamwe militia during the 1994 Rwandan conflict.